2019
DOI: 10.1109/twc.2018.2886896
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Authentication in Underwater Acoustic Sensor Networks

Abstract: With the growing use of underwater acoustic communications (UWAC) for both industrial and military operations, there is a need to ensure communication security. A particular challenge is represented by underwater acoustic networks (UWANs), which are often left unattended over long periods of time. Currently, due to physical and performance limitations, UWAC packets rarely include encryption, leaving the UWAN exposed to external attacks faking legitimate messages. In this paper, we propose a new algorithm for m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 35 publications
1
38
0
1
Order By: Relevance
“…However, it induces collision among neighboring contending device. In [15], showed that UWSN packets rarely include encryption due to physical and performance limitations. Thus, UWSN is exposed to various kind of security attack breaching legitimate message.…”
Section: Litterature Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it induces collision among neighboring contending device. In [15], showed that UWSN packets rarely include encryption due to physical and performance limitations. Thus, UWSN is exposed to various kind of security attack breaching legitimate message.…”
Section: Litterature Surveymentioning
confidence: 99%
“…These model aims to attain optimal use of available resource (spectrum). Thus, these model are referred as optimal resource allocation schemes [14,15]. In optimal resource allocation schemes, the sensor device, rather than avoiding a jammer by using different instance of spectrum, depends on exploring the existing spectrum in most resourceful way to mitigate jamming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…U DERWATER acoustic sensor networks (UASNs) are expected to play an increasingly important role in many fields, such as marine environmental monitoring, offshore exploration, auxiliary navigation, tsunami warning and marine military operations [1][2][3][4]. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the underwater acoustic channel is a public circumstance, which makes underwater acoustic communication more vulnerable to various attacks [1]. Recent studies on UANs mainly focus on network construction or protocol management [2], while only a few studies have been done on network safety [1]- [5]. Consequently, we chiefly study the safety matters for UANs in this scheme.…”
Section: Introductionmentioning
confidence: 99%